Therapeutic Experience of 189 Patients with Warthin's Tumor of the Parotid Gland - Jinnin, Tsuyoshi; Higashino, Masaaki; Nishikawa, Shuji; Terada, Tetsuya; Kawata, Ryo (International Journal of Practical Otolaryngology, 2018)
We investigated the clinical characteristics and preoperative diagnosis rate of Warthin's tumor (WT) of the parotid gland. The subjects were 189 patients who underwent surgery at the Department of Otolaryngology, Head and Neck Surgery in Osaka Medical College between September 1999 and April 2017. We compared the date of the189 patients with 466 cases of pleomorphic adenoma (PA) of the parotid gland seen during the same period. Among the 189 patients with WT, there were 163 males and 26 females, with a median age of 62 years. The sites of origin of the tumors in the parotid gland were distributed as follows: superficial lobe, 64 cases; deep lobe, 14 cases; and lower pole, 111 cases. The median maximum diameter of the tumor was 30 mm. The median operative time and the median operative blood loss were 120 minutes and 20 mL, respectively. The diagnosis had been made accurately prior to the surgery in 72% of the patients, by the fine needle aspiration cytology. Postoperative facial nerve dysfunction occurred in 39 cases (20.6%); however, it was transient in all cases. The transient facial nerve dysfunction recovered within 2 months in 50% of all cases, within 6 months in 90%, and within 1 year in 100% of cases. The features that were especially frequently encountered in the cases with postoperative facial dysfunction were origin of the tumor in the deep lobe of the parotid and large size of the tumor; furthermore, these cases also required a longer operative time. As compared with PA, WT occurred more often in male patients. WTs occurred more often in the lower pole and they were larger in size. The operative blood loss was greater. There were no significant differences with regards to the incidence of postoperative facial nerve dysfunction and the operative time.
Keywords: Warthin's tumor; parotid tumor; facial nerve dysfunction; fine needle aspiration cytology